Cattle Trade Movements: Formation of Patterns, Contact Chain and Epidemiological Risk Analysis: Minas Gerais - Brazil from 2013 to 2016. - Cardoso, Denis Lucio (2019)
The great environmental and cultural diversity found in the livestock profile, together with the size of the State, contribute to a scenario unfavourable to animal health protection. In addition to having borders bordering, in most cases, unfavourable (dry borders, where the transit of animals can be carried out on foot). The cattle trade movement is considered to be one of the main risk factors for contact-based disease introduction, handling manners and the structure of property facilities define the commercialization flow. Therefore, identifying risk areas and properties aids the maintenance and the control promoted by the Official Surveillance Department, whereas the territorial dimension makes it challenging. The advent of complex network analysis has been shown to be an advantage in safer and more optimized health defence promotion by identifying cattle trade movement patterns that can be used in disease prevention and control. Through the analysis of complex networks one can compare the behaviour of properties that participate in livestock events with ones that do not, thus, identifying properties that show greater risk. As a result, the cattle trade network in Minas Gerais presented a traffic pattern that has equivalence to other countries such as Italy, the United Kingdom and France. In that it presents a distribution that can be explained by Truncated power law. In periods preceding footand- mouth disease (FMD) vaccination campaigns the network had exhibited a greater number of active nodes with shorter contact chains, resulting in greater dispersion in that period. Short distances (less than 100 Km) had prevailed. Properties that participate in livestock events had shown higher frequencies of wider contact chains. Measures of centrality (Degree, PageRank and Betweenness) had shown to be good tools for giant component fragmentation, except for OutDegree and eigenvector. Modified weighted TOPSIS has been shown as a tool capable of incorporating the centralities, each with its qualities, into a parameter capable of identifying properties with greater risk of introduction and spread of diseases. Minas network exhibits a behaviour of resilience which deserves further investigations.